The next ship home : a novel of Ellis Island - Webb, Heather, 1976 December 30- (Sourcebooks Landmark, an imprint of Sourcebooks, 2022)
"Disembarking on Ellis Island, Francesca arrives on the shores of America with her sights set on a better life than the one she left in Italy. That same day, aspiring linguist Alma reports to her first day of work at the immigrant processing center. Ellis, though, is not the refuge it first appears thanks to President Roosevelt's attempts to deter crime. Francesca and Alma will have to rely on each other to escape its corruption and claim the American dreams they were promised. A thoughtful historical story inspired by true events, this novel probes America's history of prejudice and exclusion -- when entry at Ellis Island promised a better life but often delivered something drastically different, immigrants needed strength, resilience, and friendship to fight for their futures"--